IMPLEMENTASI SIKLUS AKUNTANSI PERUSAHAAN DAGANG BERBASIS WEB UNTUK SISWA SMKN 11 BANDUNG - Gde Agung , Anak Agung; Wisna, Nelsi; Kastaman, Kastaman; Ardiansyah, Fajri (Jurnal Abdimas Bina Bangsa, 2025)
Vocational education plays an important role in preparing young generations to face the challenges of the workforce. One of the issues faced by vocational high school accounting students is the gap between theoretical knowledge and practical application. To address this problem, Accounting Information Systems Program at Telkom University conducted a community service program by implementing a trading company accounting cycle module for students in the Accounting and Financial Institution Department at SMKN 11 Bandung. The method involved developing a module and conducting hands-on training sessions. The results showed an improvement in students' understanding of the accounting cycle, as evaluated through questionnaires, which revealed that most students found the material clear, applicable, and relevant. The training also received positive feedback despite challenges related to the duration of the sessions. This program is expected to be further developed to enhance students' readiness for the workforce or entrepreneurship.